Bradykinin B1 receptor in isolated human umbilical vein: an experimental model of the in vitro up-regulation process - Sardi Sergio Pablo; Errasti Andrea Emilse; Rey-Ares Veronica; Rogines-Velo Maria Pia; Rothlin Rodolfo Pedro (Acta Pharmacologica Sinica, 2016)
Bradykinin (BK) B1 receptors are not normally expressed in physiological conditions but could be induced in immunopathological states. Molecular approaches have confirmed that BK B1 receptor gene is transcriptionally induced in injured tissues. In these situations, the cytokine network and other proinflammatory mediators are close linked to BK B1 receptor expression. In this article, we describe the functional characterization of the BK B1 receptor up-regulation process in the isolated human umbilical vein and the pharmacological tools employed to demonstrate the de novo synthesis of these receptors. BK B1 receptors are up-regulated in a time- and protein synthesis-dependent process. Furthermore, in this tissue we have demonstrated the close link between the BK B1 receptor sensitization and proinflammatory cytokines, such as interleukin-1 beta and tumor necrosis factor-alpha. We also discuss the possible relationship between nuclear factor-kappa B and BK B1 receptor induction in human umbilical vein.